Perancangan Sistem Parkir Termonitor PC Menggunakan Teknologi RFID - Risfendra Risfendra; Rahmi Okta Tri Putri (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2020)
In general parking system is still using a manual parking system is to take the ticket to enter the parking area resulting in long queue to get into the parking area. Another problem arising from the manual parking system is the lack of information to look at the availability of empty parking spaces, making it difficult to find or just the driver to make sure their empty parking space. In anticipation of that, the tool is designed using RFID cards to enter the parking area and use the PCs to monitor the availability of parking spaces are controlled all by Arduino Mega 2560 and display on a PC using the software Visual Basic 6.0. In addition, this tool also include RGB Led display at the front entrance parking area that serves to show the state of the parking space.